Análise dos antecedentes e dos efeitos do engajamento de stakeholders na competitividade organizacional - Lima, Anderson Antônio de (2023)
The studies regarding stakeholder engagement in organizational competitiveness have presented different, often contrasting results; however, these results have not been statistically proven. Therefore, it is understood that the literature that relates these themes lacks deductive studies that actually allow for the assertion that stakeholder engagement positively affects organizational competitiveness. Additionally, it is observed that studies in this field of science have neglected the analysis of the antecedents of stakeholder engagement, causing a gap in the understanding of what the foundations of their engagement are and how these foundations influence the intensity of engagement. Therefore, this research sought to identify the antecedents and effects of stakeholder engagement on organizational competitiveness in its two main dimensions of corporate financial and corporate social performance. In the first study, the effects of stakeholder engagement on organizational competitiveness were statistically verified through a meta-analytical work, which integrated results from 54 published studies that analyzed the relationship between stakeholder engagement and organizational competitiveness. In the second study, using descriptive statistics, linear regression, and logistic regression, the influence of stakeholder engagement on corporate financial and social performance was analyzed based on financial and sustainability reports from the Economática and Global Report Institute (GRI) databases. In the third and final study, the antecedents of stakeholder engagement and possible moderators were identified by adapting existing scales, and a survey was subsequently conducted on a sample of 369 employees working in companies from various market segments. Data analysis was performed using structural equation modeling. The results showed that trust and commitment are antecedent attributes of stakeholder engagement, and with these results, managers can understand the importance of developing actions to promote these elements in their relationships with their Stakeholders. The findings of this research contribute to the refinement of stakeholder theory, more specifically, it makes it possible to corroborate theoretical studies that claim that stakeholder engagement generates positive effects on organizational competitiveness.